Glucocorticoid receptor quaternary structure drives chromatin occupancy and transcriptional outcome - Paakinaho, Ville (2019)
Most transcription factors, including nuclear receptors, are widely modeled as binding regulatory elements as monomers, homodimers, or heterodimers. Recent findings in live cells show that the glucocorticoid receptor NR3C1 (also known as GR) forms tetramers on enhancers, owing to an allosteric alteration induced by DNA binding, and suggest that higher oligomerization states are important for the gene regulatory responses of GR. By using a variant (GRtetra) that mimics this allosteric transition, we performed genome-wide studies using a GR knockout cell line with reintroduced wild-type GR or reintroduced GRtetra. GRtetra acts as a super receptor by binding to response elements not accessible to the wild-type receptor and both induces and represses more genes than GRwt. These results argue that DNA binding induces a structural transition to the tetrameric state, forming a transient higher-order structure that drives both the activating and repressive actions of glucocorticoids.